2003
DOI: 10.1002/joc.864
|View full text |Cite
|
Sign up to set email alerts
|

A sudden change in summer rainfall characteristics in Korea during the late 1970s

Abstract: We have examined long-term climate change in Korea by studying daily rainfall data over a period of 48 years . The results show that there is a more frequent heavy rainfall anomaly larger than 100 mm per 3 months in recent years. For further investigation, we divide the whole period into two 24 year intervals, 1954-77 and 1978-2001. Two well-defined rainfall peaks occur during summertime in both intervals. During the earlier interval, primary and secondary rainfall peaks are found in early July and early Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 14 publications
7
77
1
5
Order By: Relevance
“…3f) is clearly defined in temporal variations of the index, increasing by about 50% during the period. This increase in precipitation extremes over Korea adds to a consensus of previous studies (e.g., Ho et al 2003;Wang et al 2006;Kim et al 2006) which conclude that Korea has become more vulnerable to wet extremes in recent decades.…”
Section: Extreme Vulnerability In the Historical Archivesupporting
confidence: 71%
“…3f) is clearly defined in temporal variations of the index, increasing by about 50% during the period. This increase in precipitation extremes over Korea adds to a consensus of previous studies (e.g., Ho et al 2003;Wang et al 2006;Kim et al 2006) which conclude that Korea has become more vulnerable to wet extremes in recent decades.…”
Section: Extreme Vulnerability In the Historical Archivesupporting
confidence: 71%
“…Thus, there might be significant short-timescale changes in the EASM circulations, such as frequency and intensity of the synoptic-scale disturbances and typhoon activity. Interestingly, Ho et al (2003) suggested that the desertification over northern China leads to stronger and weaker convective activity over central and northern China, respectively. On the other hand, it is apparent that a significant transition in the northern spring sea surface temperatures over the equatorial Pacific is primarily responsible for the interdecadal changes in the Chinese summer rainfall through the strengthening and southward shift of the North Pacific subtropical high (Gong and Ho 2002).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The results of the analysis showed that there is a clear regime shift in 1980-1981; in addition, unlike the increasing trend (Ho et al, 2003) of summer (JJA) precipitation in Korea, post-1980 spring precipitation was reduced significantly (approximately 35 mm) compared to pre-1980. This trend was observed from 12 different weather observation stations around the country; in particular, the southwestern part (western part of the Sobaek Mountain Range) of the Korea showed the most significant decrease in the total amount of spring precipitation.…”
Section: Discussionmentioning
confidence: 88%
“…In another research, the total amounts of spring precipitation in the south China and in the central China have increased and have decreased since the late 1970s, respectively; the opposite phenomenon has been observed during summer (Yang and Lau, 2004). Compared to detailed regional studies in China, only Ho et al (2003) can be cited as a reference concerning the decadal variation (regime shift in the late 1970s) in regional precipitation in Korea, but their study only focusses on summer precipitation, thus indicating negligence of the socioeconomical importance of spring precipitation. Eventually, it is known that the climate regime shift in the spring precipitation in the East Asia, including Korea, is observed in the late 1970s or in the early 1980s.…”
Section: Introductionmentioning
confidence: 94%